Efektivitas Media Film Dalam Meningkatkan Keterampilan Menulis Narasi Siswa X Sma Negeri 1 Cina Kabupaten Bone - Nasirah; Mularahmah, Andi Sri (Arden Jaya Publisher, 2025)
Abstract This study aims to describe and test the effectiveness of film media in improving the narrative writing skills of class X students of SMA Negeri 1 Cina, Bone Regency. This study uses a quantitative approach with a Pretest-Posttest Control Group Design involving two groups, namely the experimental class given treatment using film media and the control class using conventional learning methods. The study population included all 246 class X students. The sample was determined through a random sampling technique so that 29 class X1 students were selected as the experimental group and 29 class X2 students as the control group. Data collection was carried out through a narrative writing ability test before and after treatment. Data were analyzed using descriptive statistics to see the trend of learning outcomes and inferential statistics through an independent t-test with the help of the SPSS version 20 program at a significance level of 0.05. The results of the analysis showed that students in the experimental class experienced a significant increase in writing skills compared to the control class. A total of 89.7% of students in the experimental class achieved scores above the KKM, while in the control class only 69% of students achieved that category. This significant difference is reinforced by the results of the t-test which shows a calculated t value of -6.954 greater than the t-table of 2.003 so that the null hypothesis is rejected and the alternative hypothesis is accepted. This finding confirms that the use of film media has a positive and effective effect in improving narrative writing skills. Film media can help students understand the plot, characters, settings, and atmosphere more concretely, making it easier for them to express their ideas in a more structured narrative writing form. Thus, film media is worthy of being an alternative learning strategy in teaching writing, especially in narrative writing material at the high school level. Keywords: Film Media, Narrative Writing, Learning Effectiveness.